No effects of New Zealand blackcurrant extract on physiological and performance responses in trained male cyclists undertaking repeated testing across a week period - Montanari, S.; Sahin, M. A.; Lee, B. J.; Blacker, S. D.; Willems, M. E. T. (Sports, 2020)
Anthocyanin supplements are receiving attention due to purported benefits to physiological, metabolic, and exercise responses in trained individuals. However, the efficacy of anthocyanin intake over multiple testing days is not known. We compared a placebo and two doses of anthocyanin-rich New Zealand blackcurrant (NZBC) extract (300 and 600 mg·day-1) on plasma lactate, substrate oxidation, and 16.1 km time trial (TT) performance on three occasions over 7-days in a fed state (day 1 (D1), D4, and D7). Thirteen male cyclists participated in a randomized, crossover, placebo-controlled double-blind design. There was no difference in plasma lactate and substrate oxidation between conditions and between days. A time difference was observed between D1 (1701 ± 163 s) and D4 (1682 ± 162 s) for 600 mg (p = 0.05), with an increment in average speed (D1 = 34.3 ± 3.4 vs. D4 = 34.8 ± 3.4 km·h-1, p = 0.04). However, there was no difference between the other days and between conditions. Overall, one week of intake of NZBC extract did not affect physiological and metabolic responses. Intake of 600 mg of NZBC extract showed inconsistent benefits in improving 16.1 km time trial performance over a week period in trained fed cyclists.